பண்டைத் தமிழரும் வாணிகமும் (Ancient Tamils and Trading) - Ramasamy, Krishnan (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2020)
Just like the food and other props, having and saving gold, silver and other forms of ornaments became important practices for many people. The same is true for the people of ancient Tamilnadu, who believed that agriculture, manufacturing, land and water-based trading were equally important, along the mentioned practices. For the very reason, the author claimed that our forefathers were looking for fortune even by travelling far from their homeland. In this line, the article is aimed at studying the importance of trading in the life of the ancient Tamils. The article explores the business tradition and the nature of the ancient Tamil people and their dealings with foreign nations in particular. As such, it is aimed at tracing the origin and links in the trading ties that have been established with distance nations. The article has concluded that business has occupied important proposition of their life-style and it is intertwined with the life of many Tamils who were divided along the different tinai localities. The author also argued that the Tamils ​​were prosperous businessmen, who did not deviate from the morality of the business culture. The same has been practiced among the local traders and foreigners, which placed the Tamils as one of the respected trading community, argued the paper ஆய்வுச் சுருக்கம் மக்கள் வாழ்க்கைக்கு உணவு, உடை போன்றே பொன், வெள்ளி முதலிய செல்வமும் இன்றியமையாதவையாகும். ஒரு நாட்டின் நல்வாழ்விற்கு, பொருள் வளர்ச்சிக்கு அடிப்படையாக விளங்குவன உழவுத்தொழில், கைத்தொழில்கள், நில வழியும் நீர் வழியும் நடத்தப்பெறும் வணிகம் ஆகியன என்று பண்டைத் தமிழர்கள் நன்கு அறிந்து வைத்திருந்தனர்; ஆகையால்தான், நம் முன்னோர் தம் மக்களைத் திரை கடல் ஓடியும் திரவியம் தேடு என்றனர் போலும் எனும் அடிப்படையில், இந்தக் கட்டுரை பண்டைய தமிழ் மக்களின் வணிகம், அவர்கள் பிற நாடுகளுடன் மேற்கொண்ட வாணிகம் முதலியவற்றைப் பற்றி ஆராய்கிறது என விளக்கியுள்ளார். பண்டைத் தமிழர் சமுதாயத்தில் வணிகர் உயர்ந்த இடத்தைப் பெற்றிருந்தது எனவும் சங்ககால வாணிகம் தமிழர்களின் வாழ்க்கையோடு பின்னிப்பிணைந்தது எனவும், வணிகம் ஐவகை நிலங்களில் வெவ்வேறு தொழில்கள் நடைபெற்றதால் வாணிகமும் வேறுபட்டு இருப்பதைக் காண முடிகிறது எனக் கூறியுள்ளார். வணிகர்களால் தமிழகம் செல்வச் செழிப்புற்று விளங்கியது எனவும், இவர்கள் சான்றோர்கள் கூறியுள்ள அறநெறிகளிலிருந்து தவறாது, இல்லற நெறியிலும் பிறழாது வாழ்ந்தனர். வெளிநாட்டினரோடு சிறப்பாக வாணிகம் செய்தனர் என விளக்கியுள்ளார்.